A Quantitative Study of Green Marketing Perceptions Among Kathmandu Valley College Students - Ayer, Sarita Kumari; Shrestha, Puja; Karki, Rojina; Shrestha, Rose Kumar; Gurung, Sambridhi; Tamang, Shiwani; Choudhary, Satyanarayan (International Journal of Atharva, 2025)
Background: Green marketing is increasingly pivotal in Nepal, particularly in the Kathmandu Valley, as consumer environmental awareness grows. Understanding the perceptions of key demographics like university students is crucial for businesses developing effective sustainability strategies. Objectives: This study aimed to assess university students’ perceptions of green marketing in the Kathmandu Valley and to examine the differences in these perceptions based on gender. Methods: A quantitative, descriptive, and comparative research design was employed. Data were collected via a structured questionnaire from 205 randomly selected university students. Analyses were conducted using SPSS, utilizing descriptive statistics and an independent samples t-test to compare male and female responses. Findings: The results revealed overwhelmingly positive perceptions of green marketing among students. A significant majority expressed a preference for eco-friendly brands, acknowledged the influence of green advertisements, trusted sustainability certifications, and were willing to pay a premium for genuine sustainable products. However, skepticism about greenwashing was also prevalent. Crucially, a significant gender difference was found, with female students demonstrating more favorable perceptions of green marketing than their male counterparts (p = 0.033). Conclusion: University students in the Kathmandu Valley are generally receptive to green marketing. The significant gender gap suggests tailored marketing approaches are necessary. Despite positive attitudes, challenges like consumer skepticism toward greenwashing persist. Implication: Marketers should develop transparent, credible green marketing campaigns to build trust and bridge the value-action gap. Strategies should be gender-sensitive, with messaging potentially more focused on platforms and values that resonate with female consumers.